БРОНХИАЛ АСТМА БИЛАН КАСАЛЛАНГАН БЕМОРЛАРНИНГ ПСИХО-ЭМОЦИОНАЛ ХУСУСИЯТЛАРИ - Нарметова, Ю.К. (SCIENCE and SOCIETY, 2020)
The article touches on the psycho-emotional state of patients with bronchial asthma. A characteristic feature of a patient with bronchial asthma is that they experience and express more negative emotions than other people. They are also insufficiently resistant to stress and infantilism, characterized by a lack of self-esteem, which is mainly low self-esteem and is highly dependent on the opinions of others.